Women's empowerment and experiences of mistreatment during childbirth in facilities in Lucknow, India: results from a cross-sectional study - Nadia Diamond-Smith; Emily Treleaven; Nirmala Murthy; May Sudhinaraset (BMC, 2017)
Abstract Background Recent evidence has found widespread reports of women experiencing abuse, neglect, discrimination, and poor interpersonal care during childbirth around the globe. Empowerment may be a protective mechanism for women against facility mistreatment during childbirth. The majority of previous research on mistreatment during childbirth has been qualitative in nature. Methods In this analysis, we use quantitative data from 392 women who recently gave birth in a facility in the slums of Lucknow, India, to explore whether measures of women's empowerment are associated with their experiences of mistreatment at their last childbirth. We use the Gender Equitable Men (GEM) scale to measure women's views of gender equality. Results We find that women who had more equitable views about the role of women were less likely to report experiencing mistreatment during childbirth. These findings suggest that dimensions of women's empowerment related to social norms about women's value and role are associated with experiences of mistreatment during childbirth. Conclusions This expands our understanding of empowerment and women's health, and also suggests that the GEM scale can be used to measure certain domains of empowerment from a women's perspective in this setting.